2011
DOI: 10.3340/jkns.2011.50.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Factors Affecting Clinical Outcomes for Saccular Aneurysms of Posterior Inferior Cerebellar Artery with Subarachnoid Hemorrhage

Abstract: study that analyzed the predicting factors of clinical outcome 13) . We experienced 20 patients for PICA aneurysms with subarachnoid hemorrhage (SAH). And so, we investigated the clinical outcomes after surgery and endovascular treatment and tried to find the predicting factors affecting the outcomes for ruptured PICA aneurysms. MATERIALS AND METHODS Patient populationsBetween April 1996 and December 2010, 1960 intracranial aneurysms were treated at our institution. Among them, we retrospectively reviewed 20 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…8) Another study that compared direct surgery and endovascular treatment reported that the factors related to poor outcomes were the severity of the subarachnoid hemorrhage and the presence or absence of acute hydrocephalus, and they reported that there was no difference in the outcomes between direct surgery and endovascular treatment. 6) Our patient also showed a rapid decline in the level of consciousness accompanied by marked intraventricular hematoma after rupture, suggestive of a rapid increase in posterior cranial fossa pressure, as described in previous reports. In addition, Sejkorová et al 15) reported that ruptured distal PICA aneurysms should be treated early after the onset because the re-rupture rate before treatment was found to be higher for these aneurysms as compared to aneurysms at other sites, such as supratentorial aneurysms.…”
Section: Direct Surgery and Endovascular Treatmentsupporting
confidence: 88%
See 2 more Smart Citations
“…8) Another study that compared direct surgery and endovascular treatment reported that the factors related to poor outcomes were the severity of the subarachnoid hemorrhage and the presence or absence of acute hydrocephalus, and they reported that there was no difference in the outcomes between direct surgery and endovascular treatment. 6) Our patient also showed a rapid decline in the level of consciousness accompanied by marked intraventricular hematoma after rupture, suggestive of a rapid increase in posterior cranial fossa pressure, as described in previous reports. In addition, Sejkorová et al 15) reported that ruptured distal PICA aneurysms should be treated early after the onset because the re-rupture rate before treatment was found to be higher for these aneurysms as compared to aneurysms at other sites, such as supratentorial aneurysms.…”
Section: Direct Surgery and Endovascular Treatmentsupporting
confidence: 88%
“…The general sites of PICA aneurysms are classified as follows: 1) the anterior medullary segment, 2) lateral medullary segment, 3) tonsillomedullary segment, 4) telovelotonsillar segment, and 5) cortical segment. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] On the basis of this classification, we evaluated the factors to be considered while selecting the treatment methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is information about Op-Mo in 14 of them, but only 9 of them contain events [11,14,16,22,24,[26][27][28][29]. Twelve contain information about PND and 11 of them demonstrate events [11,12,14,17,[22][23][24][26][27][28][29]. Out of the 10 articles giving information about La-Mo, there is only two including an event [18,22].…”
Section: Resultsmentioning
confidence: 99%
“…The articles which were excluded from that article pool were those which focused on the reoperation management, case reports, systematic reviews, unrelated outcome, co-morbidities, experimental techniques, or one of the two techniques and all those which demonstrated mixed or unclear results, being separated between anterior and posterior circulation. The final article pool contained 20 articles, as appropriate for our meta-analysis [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%